2016
DOI: 10.1136/annrheumdis-2016-209668
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of an interleukin 6 monoclonal antibody for the treatment of systemic lupus erythematosus: a phase II dose-ranging randomised controlled trial

Abstract: ObjectivesThis phase II trial evaluated the efficacy and safety of an interleukin (IL) 6 monoclonal antibody for systemic lupus erythematosus (SLE).MethodsPatients with active disease were randomised to placebo or PF-04236921 10 mg, 50 mg or 200 mg, subcutaneously, every 8 weeks with stable background therapy. SLE Responder Index (SRI-4; primary end point) and British Isles Lupus Assessment Group-based Composite Lupus Assessment (BICLA) were assessed at week 24. Post hoc analysis identified an enriched populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 34 publications
(29 reference statements)
3
66
0
Order By: Relevance
“…Several elements of the immune system are potential targets for therapeutic intervention in patients with SLE. In this sense, IL‐6 is implicated in the development and progression of SLE in mice and it is identified as one of the major genetic risk factors for SLE in humans ; thus, its modulation seems to be a potential therapeutic approach in SLE management . In the present study, we found a remarkable increase of IL‐6 production in patients with SLE compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Several elements of the immune system are potential targets for therapeutic intervention in patients with SLE. In this sense, IL‐6 is implicated in the development and progression of SLE in mice and it is identified as one of the major genetic risk factors for SLE in humans ; thus, its modulation seems to be a potential therapeutic approach in SLE management . In the present study, we found a remarkable increase of IL‐6 production in patients with SLE compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 63%
“…Targeting IL‐6 signaling may offer a novel therapeutic approach for SLE since IL‐6 is critically involved in the B cell hyperactivity of SLE and it may also mediate tissue damage in this disease . In our study, we examined IL‐6 induced production on PBMC isolated from patients with SLE and healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, serum C‐reactive protein (CRP), whose hepatic production is predominantly mediated by IL6 , was used as the pharmacology marker for PF‐04236921. Overall, PF‐04236921 demonstrated desirable pharmacokinetic (PK) and pharmacodynamic (PD) properties supporting sustained target inhibition, and low incidence of immunogenicity upon single and multiple dose administrations . Efficacy and safety findings were discussed previously.…”
Section: Introductionmentioning
confidence: 83%
“…In view of the emerging use of ANA testing in the trial setting, we have therefore extended this investigation to specifically assess responses of patients with sufficient disease activity for clinical trial eligibility. For this purpose, we evaluated samples from a phase II study of a monoclonal antibody to interleukin‐6 (IL‐6) . At study enrollment, 23.8% of the patients had a negative ANA value at 1:80 dilution as assessed at the central laboratory, although a detailed review of medical records by experts confirmed historically positive ANA status and clinically active disease.…”
Section: Introductionmentioning
confidence: 99%